The Impact of Aging and Progressive Neurological Disease on Swallowing: A Concise Overview. Issue 4 (25th April 2016) - Britton, Deanna
Abstract: Difficulty with swallowing, also known as "dysphagia, " is a common consequence of neurologic disease, including a variety of progressive neurologic diseases associated with aging. The effects of various neurogenic degenerative diseases on swallowing may differ substantially, depending on the nature of the condition. However, the process of aging alone also has an impact on swallowing function. In this concise review, a brief overview of normal swallowing and changes in swallowing associated with aging will be presented. This will be followed by a discussion of the additional impact of neurodegenerative diseases associated with aging on swallowing. Practical Applications: Many of the neurodegenerative diseases are prevalent in the aging population. For aging individuals, the impact of the neurodegenerative disease on swallowing is overlaid upon and may interact with the impact of aging on swallowing. In order to effectively assess and treat these individuals, it is critical to understand both the impact of aging and the underlying pathology of the disease itself.